2012
DOI: 10.1063/1.4705296
|View full text |Cite
|
Sign up to set email alerts
|

Impact and wetting behaviors of impinging microdroplets on superhydrophobic textured surfaces

Abstract: The impact and wetting behaviors of impinging microdroplets on textured surfaces are investigated using high-speed imaging. Microdroplets with diameters less than 50 μm are ejected using a piezoelectric printhead with controlled Weber numbers. The impact behaviors are clearly observed, and the detailed mechanisms are explained according to the Weber number and wetting states of the impinging droplets. Moreover, the transition phenomena from bouncing to non-bouncing are clearly observed. The impalement transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…For all surfaces the advancing angle is around 160° and the difference in hysteresis originates only from the receding angle. This is in agreement with previous findings for drops in the Cassie Baxter state rolling off the surface [13,14].. To optimize the geometry for increased water repellency one normally decreases the surface coverage of structures in contact with the water at the cost of decreasing the stability of the Cassie Baxter state [15]. For the random multi-height structures, we see that this in addition seems to lead to an increased hysteresis.…”
Section: Resultssupporting
confidence: 82%
“…For all surfaces the advancing angle is around 160° and the difference in hysteresis originates only from the receding angle. This is in agreement with previous findings for drops in the Cassie Baxter state rolling off the surface [13,14].. To optimize the geometry for increased water repellency one normally decreases the surface coverage of structures in contact with the water at the cost of decreasing the stability of the Cassie Baxter state [15]. For the random multi-height structures, we see that this in addition seems to lead to an increased hysteresis.…”
Section: Resultssupporting
confidence: 82%
“…Different from the Bartolo et al's work, researchers found that the calculated antiwetting capillary pressure ( P C ) far exceeded the value of calculated dynamic pressure ( P D ) by Equations and , which cannot explain the wetting transition . The significant role of water hammer pressure ( P WH ) was then demonstrated in the transition to the Wenzel state . The water hammer pressure ( P WH , in Equation ) was explained by the one needed to produce a radius R WH (Equation ) at the contact area:PWH=kρVCRWH=R0VCwhere k stands for a constant determined by the type of impacting surface, shape, and velocity of the droplet, C for the speed of sound, and R 0 for the initial droplet radius.…”
Section: The Mechanisms Of Anti‐icing and Icephobicitymentioning
confidence: 85%
“…Irreversible transition between Cassie and Wenzel will bring the loss of the antiadhesive performances related with superhydrophobicity, and have an adverse effect on the anti‐icing property . However, the mechanism of Cassie–Wenzel transition is still in a heated discussion.…”
Section: The Mechanisms Of Anti‐icing and Icephobicitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, a transition between the Cassie-Baxter state and the Wenzel state can easily occur for several reasons, including droplet evaporation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%